HUBUNGAN SIKAP IBU TERHADAP PENDIDIKAN SEKS DENGAN PEMBERIAN INFORMASI TENTANG SEKSUALITAS PADA PRA REMAJA PUTRI USIA 10-12 TAHUN - Aih Alawiyah Madjid; Tati S. D; Nani N. Djamal (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Parents are seen as role model and important figures in family whom responsible to teach and facilitate a suitable education model for their children. Children need many information and knowledge that would help them to solve all problems the face in their life. Pre adolescence children, especially young teenage girl in this case would need an appropriate sex education to help help them pass through their problems and social interaction life. This information was best given to them by mothers since children would felt safer with same sex beside this also could give other diversion about sexuality values adopted in society. Aside from it, there also a condition that many mothers felt that sex education was taboo and it was also caused by little information and knowledge those mothers had. At this point, mother’s perception and parent’s personal feeling have constructed a negative set of mind towards sex educationFrom this phenomenon, this research was conducted to analyze the correlation between mother’s attitude towards sex education with information given and taught by them for young teenage girl between the age 10-12 years old. The datas gathered for this research were taken from sample of young teenage girls’ mothers living at community housing complex in Tasikmalaya. The methods used in this research is correlational model which was used to analyze variables that caused the phenomenon and also try to find out the relationship between one variabel with another.In this case study, we have made a specific assumptions to formulize a hypothese which then were tested to acquire a valid and reliable data from raw data using Spearman Rank’s statistical analysis since both variables were ordinal and have a significancy level of 5 percent. Statistic analysis conducted in this research then resulted in correlation coefficient of 0,424 with an error margin of 0,003—which means that the hypothese is accepted. A brief conclusion that can be taken from this research is that parent’s (mothers) educational background have great influence on their attitude toward sex education—which is—the higher the education those mothers had, the more positive they felt toward sex education.